Common Ground or Double Bind? The Possibility of Dialogue in Plato’s Crito - Feldman, Sarah (2022)
Much recent scholarship on Plato’ Crito has revolved around the controversy about the relationship and possible compatibility between the arguments Socrates gives in his own person (SocratesS) and those he gives in the person of the Laws (SocratesL). By contrast, the relation between the arguments given by SocratesL and those given by Crito continues to be seen as uncontroversial: by the end of the dialogue, commentators agree, Crito has no choice but to concede to the force of SocratesL’s arguments. Against this traditional reading, this paper will argue not only that SocratesL’s arguments fail to secure Crito’s agreement, but also that two characters’ attempts to communicate end at an impasse that seems to leave little room for meaningful shared discourse –and may even undermine Crito’s belief in the possibility of meaningful speech. My interpretation is informed by Socrates’ account (at 49c9-e3) of the need for and nature of a “common ground” as a requisite for genuine dialogue. This passage, I argue, challenges the traditional analysis of Crito as the representative of a particular value system or a particular “type”, demanding, instead, a consideration of the effect of Socrates’ arguments upon Crito in light of a more robust view of the latter’s perspective. Such a reconsideration has consequences not only for our appreciation of the dramatic structure of the dialogue, but also for how we understand one of the dialogue’s central, if underexplored, themes: the belief in a shared logos and the psychagogic necessity and perils of testing that belief.